Efeitos de um programa de treinamento circense em neutrófilos de crianças eutróficas ou com excesso de peso - Caçula, Kim Guimarães (2019)
Currently, obesity is considered a serious public health problem worldwide and it is known that this condition induces a pro-inflammatory state in obese individuals. Despite the recent discoveries on the role of immune system cells in obesity, the role of neutrophils in inflammation induced by obesity not fully understood yet. Moreover, it is proven that physical exercise have a modulating effect on obesity and in immune system cells and it has already been shown that the intensity and duration of physical exercise may influence the functions and apoptosis of neutrophils, but few studies have investigated the role of neutrophils in overweight children. Therefore, the purpose of this work was to evaluate the role of neutrophils in overweight and eutrophic children practitioners and nonpractitioners of circus activity. For this, two groups of children (from 7 to 12 years old) were submitted to a period of circus activity and anthropometric analyzes and neutrophils obtained from peripheral blood were made before and after this period. In relation the anthropometric measurements, we did not observe a decrease in body fat percentage values after the training period, but there was an increase in lean mass in both groups after the period of practice of circus exercises. In addition, this exercise was able to modify the activity of neutrophils, since that increased the expression of CD95 and decreased ERO production even after PMA stimulation, increased phagocytosis in the eutrophic group and decreased the production of inflammatory cytokines, thus showing that this type of physical exercise can modify the function of the cells of the immune system.